Translation, cultural adaptation and validation of the Italian version of the Brief Index of Lupus Damage: the BILDit. (September 2020) - Elefante, Elena; Tani, Chiara; Santoni, Adele; Lorenzoni, Valentina; Stagnaro, Chiara; Parma, Alice; Ferro, Francesco; Carli, Linda; Signorini, Viola; Zucchi, Dina; Doherty, Wendy; McSorley, Mary Rose; et al.
Objectives: The Brief Index of Lupus Damage (BILD) is an instrument of self-evaluation of organ damage for systemic lupus erythematosus (SLE) patients. The objectives of this study were the translation, cultural adaptation and validation of the Italian version of the BILD (BILDit). Methods: The process of translation and cultural adaptation followed published guidelines. The BILDit was pretested in a pilot study with 30 SLE patients in order to evaluate acceptability, reliability, comprehension and feasibility, and then validated in consecutive SLE patients attending our clinic. Results: A total of 167 SLE patients were enrolled. In the pilot study, the BILDit demonstrated good acceptability, feasibility and comprehensibility and a very high degree of reliability (Cronbach's α = 1). In the validation cohort, the BILDit showed a significant positive correlation with the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI; ρ = 0.69; p < 0.001). Analysing the item-by-item correlation between the BILDit and the SDI, a good correlation ( p < 0.001) was found for 73.1% of the items. In the multivariate analysis, the BILDit showed a significant positive correlation with age and disease duration ( p < 0.01). Conclusions: The BILDit seems to be an acceptable and reliable instrument for patient self-evaluation of disease damage, with a good correlation with the SDI. It can be considered as a screening tool for the evaluation of organ damage starting from the patient's perceptive.